Potential for Ketotherapies as Amyloid-Regulating Treatment in Individuals at Risk for Alzheimer’s Disease - Taylor, Matthew K.; Sullivan, Debra K.; Keller, Jessica E.; Burns, Jeffrey M.; Swerdlow, Russell H. (Frontiers in Neuroscience, 2022)
Alzheimer’s disease (AD) is a progressive neurodegenerative condition characterized by clinical decline in memory and other cognitive functions. A classic AD neuropathological hallmark includes the accumulation of amyloid-β (Aβ) plaques, which may precede onset of clinical symptoms by over a decade. Efforts to prevent or treat AD frequently emphasize decreasing Aβ through various mechanisms, but such approaches have yet to establish compelling interventions. It is still not understood exactly why Aβ accumulates in AD, but it is hypothesized that Aβ and other downstream pathological events are a result of impaired bioenergetics, which can also manifest prior to cognitive decline. Evidence suggests that individuals with AD and at high risk for AD have functional brain ketone metabolism and ketotherapies (KTs), dietary approaches that produce ketone bodies for energy metabolism, may affect AD pathology by targeting impaired brain bioenergetics. Cognitively normal individuals with elevated brain Aβ, deemed “preclinical AD”, and older adults with peripheral metabolic impairments are ideal candidates to test whether KTs modulate AD biology as they have impaired mitochondrial function, perturbed brain glucose metabolism, and elevated risk for rapid Aβ accumulation and symptomatic AD. Here, we discuss the link between brain bioenergetics and Aβ, as well as the potential for KTs to influence AD risk and progression.